PENGARUH TINGKAT PERPUTARAN PIUTANG DAN TINGKAT PROFITABILITAS TERHADAP TINGKAT SISA HASIL USAHADI KPRI KOMPAK PURWOREJO (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
The purpose of this study is to find out how big the influence of receivable turnover rate and profitability level limited by ROA to the amount of the rest of the business results produced KPRI Kompak Purworejo. The data used is secondary data derived from KPRI KOMPAK financial statements in the period 2011 to 2016 obtained by researching directly. Data analysis techniques in this study using multiple regression analysis, t test, F test and the coefficient of determination and use the computer application tools Statistical Package for the Social Sciences (SPSS) version 16.0.The result of analysis based on calculation using multiple regression test obtained equation as follows: Y =-0,957 + 0,256 X1- 20,313 X2. The magnitude of the coefficient of determinat ion - 0.175 or equal denagn-17%. Partially there is no significant influence between the level of receivables and profitability of the level of SHU.Secara simultant turnover rate and profitability level does not significantly affect the level of SHU.In the study, obtained a decrease SHU resulting in minus data that is on the factor level SHU on 2015.